Sonochemical synthesis, structural inspection and semiconductor behavior of three new nano sized Cu(II), Co(II) and Ni(II) chelates based on tri‐dentate NOO imine ligand as precursors for metal oxides. (8th December 2017) - Abdel Rahman, Laila H.; Abu‐Dief, Ahmed M.; El‐Khatib, Rafat M.; Abdel‐Fatah, Shimaa Mahdy; Adam, A.M.; Ibrahim, E.M.M.
Abstract : Three novel nanosized Cu(II), Co(II) and Ni(II) complexes of imine ligand attained from the condensation of 2‐amino‐3‐hydroxypyridine and 3‐methoxysalicylaldehyde have been prepared and investigated using diverse chemical methods such as NMR, CHN analysis, conductance, IR, Spectral studies, TGA and magnetic moment measurements. The obtained data confirmed that the synthesized complexes have metal: ligand ratio of 1:1 and octahedral geometry for Co(II) and Ni(II) complexes. Interestingly, The complexes are used as precursors for producing CuO, Co2 O3 and NiO nanoparticles by calcination at 500 °C and their structures were described by powder x‐ray and transmittance electron microscopy. Furthermore, to investigate the feasibility of using the synthesized materials for semiconductor based nanodevices, the electrical properties of the prepared imine complexes and their corresponding metal oxides were investigated by measuring the electrical conductivity over a temperature range 373‐593 K. The data confirm that the materials are semiconductor. The electrical conduction process in the complexes is governed by intermolecular and intramolecular transfer of the charge carriers. But, the conduction mechanism arises from the contribution of the phonon‐assisted small polaron hopping in NiO nanoparticles and charge carrier hopping in CuO and Co2 O3 nanoparticles. The results indicate that the complexes under study are promising candidates for wide scale of organic based semiconducting devices. Abstract : Three novel nanosized Cu(II), Co(II) and Ni(II) complexes of imine ligand and their corresponding metal oxides nanoparticles were synthesized and characterized via different tools. the feasibility of using the synthesized materials for semiconductor based nanodevices, were investigated by measuring the electrical conductivity over a temperature range 373–593K. The results indicate that the complexes under study are promising candidates for wide scale of organic based semiconducting devices.